Bilateral agreement for academic years 2010/2013 Socrates Programme (Higher Education Erasmus) between Universidade Lusíada de Lisboa and Université Nancy - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within Lifelong Learning Programme. - Erasmus subject area: Psychology.